Sistem Pengolahan Air Limbah PT Evonik Indonesia Plant Cikarang - Ari Setiawan Sholikhin; Putri Nika Andini Hidayat; Sinta Salsabilla Aditya; Dodit Ardiatma (DPPM Universitas Pelita Bangsa, 2022)
Evonik Indonesia is a company located in the Jababeka 1 Industrial Estate which focuses its activities on the manufacture of chemicals, especially hydrogen peroxide (H2O2). PT. Evonik Indonesia in addition to producing H2O2 also produces waste or waste. One of the wastes produced is liquid waste containing H2O2, organic substances and dissolved solids. In order for the liquid waste produced to meet the quality standards that have been set, it is necessary to treat the liquid waste. Waste treatment is carried out physically and chemically with the aim of neutralizing acid and alkaline waste, assisting the sludge separation process, separating dissolved solids, reducing oil concentration, increasing flotation and sedimentation efficiency and oxidizing colors and toxic substances. The method used in this research is an observational survey with a descriptive approach where the results of the observations state that the results of waste treatment at PT. Evonik Indonesia still tends to fluctuate and some of them still exceed the quality standard of PT. Jababeka Infrastructure. Keywords: Liquid Waste, H2O2, Factory, Environment